PHYTOCHEMICAL STUDY OF COMFREY (SYMPHYLUS OFFICINALE L.) ROOT EXTRACTS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The purpose of the present study was to determinate the biologically active substance in 95% ethanol and subsequent water extracts from Bulgarian comfrey (Symphylus officinale L.) roots and to evaluate their antioxidant potential. The antioxidant activity was evaluated by several reliable methods such as DPPH-, ABTS-, FRAP-, CUPRAC-, ORAC and HORAC-assays, as well as the total phenolic content. In addition, the total organic, fructose and sugar content were determined by spectrophotomeric and HPLC-RID methods. The level of fructans in ethanol extracts was 25.2 g/100g dry weight, as nystose and 1-kestose were only 0.1g/100g dry weight, and 0.3g/100g dry weight, respectively. The absence of fructooligosacharides in water extracts after the ethanol pretreatment was established. Inulin content was evaluated to be 25.2 g/100 g dry weight. In addition, total uronic content was established to be 2.0 g/100 g dw as its level dominated in water extracts – 1.7 g/100 g dw, respectively. The metabolite profile of roots revealed their potential application as radical scavengers due to the presence of polyphenols. Phenolic acids (neochlorogenic, p-coumaric and gallic acids) and flavonoids (quecetin, myrecitin and naringin) were the dominant polyphenols in comfrey extracts. Therefore, the root extracts of Symphylus officinale L. could be assumed as a rich source of biologically active substance, in particular dietary fiber with potential prebiotic effect, due to the presence of polysaccharide inulin and fructooligosacharides.